The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1016/0735-1097(93)90685-t
|View full text |Cite
|
Sign up to set email alerts
|

Isolated ultrafiltration in moderate congestive heart failure

Abstract: In patients with moderate congestive heart failure, ultrafiltration reduces the severity of the syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
2
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 33 publications
4
89
2
2
Order By: Relevance
“…23,27-31 UF improves cardiac filling pressures, 28,29,[32][33][34][35] symptoms, exercise capacity, 32,33,36,37 and renal perfusion. 38 Serum sodium also improves…”
Section: Clinical Experience With Uf For Hfmentioning
confidence: 99%
“…23,27-31 UF improves cardiac filling pressures, 28,29,[32][33][34][35] symptoms, exercise capacity, 32,33,36,37 and renal perfusion. 38 Serum sodium also improves…”
Section: Clinical Experience With Uf For Hfmentioning
confidence: 99%
“…UF therapy was initially explored in a series of interesting studies in Europe trying to elucidate its underlying mechanisms of action in the setting of ADHF, while simultaneously exploring its cardiorespiratory effects (11)(12)(13). Because exacerbation in neurohormonal activity is considered a key pathway in development, progression, and prognosis of HF, it was the focus of several UF studies.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…Compared with ongoing medical therapy, patients treated with ultrafiltration experienced improved hemodynamics, diastolic filling parameters, neurohormonal responsiveness, and exercise capacity. 34,36 A similar trial was subsequently performed with an active control arm by the same investigative team. Sixteen patients with mild heart failure were randomized to ultrafiltration (500 mL/hr) versus IV furosemide (IV bolus followed by continuous infusion-average dose 248 mg).…”
Section: Ultrafiltration Is the Preferred Initialmentioning
confidence: 99%
“…32 In contrast to the adverse physiological consequences of loop diuretics, numerous studies have demonstrated favorable responses to ultrafiltration. Such studies have shown that removal of [33][34][35][36][37][38][39][40][41][42][43][44][45][46] The evidence base supporting the use of ultrafiltration is superior to that for loop diuretics. There are 5 randomized controlled trials of ultrafiltration in patients with heart failure.…”
Section: Ultrafiltration Is the Preferred Initialmentioning
confidence: 99%